2006
DOI: 10.1002/yea.1428
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and carbon source‐regulated expression of PDC and ADH genes in the respiratory yeast Pichia anomala

Abstract: We amplified, sequenced and studied the transcriptional regulation of genes of the alcoholic fermentation pathway in the biocontrol and non-Saccharomyces wine yeast, Pichia anomala. Two ADH isogenes, PaADH1 and PaADH2, and one PDC gene, PaPDC1, were amplified from genomic P. anomala DNA by a two-step PCR approach, using degenerated primers against conserved regions of the respective genes for cloning core regions, and PCR-based gene walking for cloning the respective 5 and 3 -ends. According to sequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The mRNA levels of the grg2 gene decreased dramatically when glucose was added to the culture. Moreover, the PDC gene was induced by glucose, as it is in the majority of phylogenetically related organisms [22-25]. In addition, we found that adding glucose to the media caused a decrease in the mRNA levels of all of the carotenogenesis genes involved in the synthesis of astaxanthin from GGPP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The mRNA levels of the grg2 gene decreased dramatically when glucose was added to the culture. Moreover, the PDC gene was induced by glucose, as it is in the majority of phylogenetically related organisms [22-25]. In addition, we found that adding glucose to the media caused a decrease in the mRNA levels of all of the carotenogenesis genes involved in the synthesis of astaxanthin from GGPP.…”
Section: Discussionmentioning
confidence: 86%
“…This gene is highly repressed by glucose in N. crassa and in many other yeasts [20,21]. As a glucose induction control, we used the pyruvate decarboxylase gene PDC , which is induced by glucose in several fungi and yeasts [22-25]. For this experiment, genomic PDC and its cDNA were sequenced, its intron-exon structure was determined and its sequence was deposited in the database [GenBank: HQ694557 and HQ694558].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the expression regulation and the physiological function of the CmADH1/CmADH2A system in C. maltosa were essentially similar to those of the ScADH1/ScADH2 system in S. cerevisiae during glucose metabolism [6], [33]. In contrast, the ancestral yeast species seems to contain one cytoplasmic ADH [18], and a dual function of an ADH gene responsible for both formation and consumption of ethanol have been described for PsADH1 of P. stipitis [7], PaADH1 of Pichia anomala [34] and CaADH1 of C. albicans [14]. Gene duplications lead to the modern ADH system composed of more than one ADH genes during yeast evolution (Figure 1).…”
Section: Discussionmentioning
confidence: 95%
“…Fredlund et al (2004a) reported that P. anomala exhibited growth rates of 0.22 and 0.056 h -1 and biomass yields of 0.59 and 0.11 g/g glucose under aerobic and anaerobic conditions, respectively. When shifted to oxygen limitation, P. anomala rapidly induced key fermentative enzymes (pyruvate decarboxylase and alcohol dehydrogenase- Fredlund et al 2006) and also lowered flux through the pentose phosphate pathway. S. cerevisiae is also regarded as a facultative yeast, but in this organism, glucose (rather than oxygen) governs central carbon metabolism.…”
Section: P Anomala In Industrymentioning
confidence: 99%